Impact of Goods and Services Tax Bill on the Indian Economy - Shokeen, Seema; Banwari, Vijeta; Singh, Pooja (Indian Journal of Finance, 2017)
The Goods and Services Tax Bill or GST Bill is officially also known as The Constitution (One Hundred Twenty Second Amendment) Act, 2016 which proposes a national value added tax to be applied in India from July 1, 2017. The GST bill was initially accepted in the Lok Sabha on March 29, 2017 and got its final acceptance in the Rajya Sabha on April 6, 2017.Goods and Services Tax (GST) is an all-inclusive tax levied on manufacture, sale, and consumption of goods and services at a nationwide level. GST is considered to be a mechanism to enforce the indirect tax on manufacturing, sales, and consumption of goods and services across India, to replace the existing taxation schemes implemented by the Central and State governments. The simplicity of this tax would lead to easy administration and enforcement of the tax. The biggest advantage of the GST is estimated to be inÂ terms of the reduction in the overall tax paid by the consumer currently, free movements of the goods from one state to another, and minimization in the paperwork up to a large extent. This paper analyzed the effect of the GST Bill on the Indian economy in general and for small, medium, and large enterprises in specific. The study was based completely on hypothetical knowledge as the GST Bill has not been introduced as yet. In the light of ongoing discussion surrounding the GST Bill, this paper took a few cases to compare GST and the expected impact post GST. This study would be extremely relevant as it forecasted the impact of the proposed GST Bill.